2015
DOI: 10.3835/plantgenome2015.06.0045
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Barley Genome Zipper and Genomic Resources for Breeding Purposes

Abstract: The aim of this study was to estimate the accuracy and convergence of newly developed barley (Hordeum vulgare L.) genomic resources, primarily genome zipper (GZ) and population sequencing (POPSEQ), at the genome-wide level and to assess their usefulness in applied barley breeding by analyzing seven known loci. Comparison of barley GZ and POPSEQ maps to a newly developed consensus genetic map constructed with data from 13 individual linkage maps yielded an accuracy of 97.8% (GZ) and 99.3% (POPSEQ), respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 123 publications
1
12
0
Order By: Relevance
“…Some positions of Morex WGS contigs were not in agreement with the genotypes of our lines. Differences in collinearity between several genetic maps and the POPSEQ reference have been already described (Cantalapiedra et al, 2015;Silvar et al, 2015). These incongruences are important for fine mapping purposes.…”
Section: Discussionmentioning
confidence: 93%
“…Some positions of Morex WGS contigs were not in agreement with the genotypes of our lines. Differences in collinearity between several genetic maps and the POPSEQ reference have been already described (Cantalapiedra et al, 2015;Silvar et al, 2015). These incongruences are important for fine mapping purposes.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it is difficult to directly use the data from the wheat Genome Zipper in our research, like a previous report regarding the positional isolation of powdery mildew QTLs in barley [ 57 ]. Successful fine mapping of quantitative trait loci by using the synteny-based or zipper-based markers combined with primarily genome zipper and population sequencing analysis has been reported [ 58 , 59 ]. Based on previous research, 97 gene were identified according to our synteny analysis with EST-STS markers.…”
Section: Discussionmentioning
confidence: 99%
“…The whole set of genotypes was analysed with the Infinium 9 k iSelect Chip (Illumina, San Diego, CA, USA). For mapping, a recent consensus map of single nucleotide polymorphism (SNP) markers by Silvar, et al [40] was used. After filtering for >5% minor allele frequency (MAF), <10% missing values and <5% heterozygous markers, 4438 SNP markers were used to construct a HapMap and to calculate a kinship of Roger's distances [74] in the open, web-based platform Galaxy [75][76][77].…”
Section: Methodsmentioning
confidence: 99%
“…Genotypic data can be generated applying e.g., next generation sequencing (NGS) [34,35], high throughput array technologies like the Infinium iSelect assay by Illumina [36], the Axiom technology by Affymetrix [37] or genotyping by sequencing (GBS) [38,39], resulting in high density genetic maps, e.g., published by Silvar, et al [40]. Quantitative trait loci (QTL) for water use related traits under drought stress treatment in barley were identified e.g., by Varshney, et al [41] for biomass on barley chromosome 3H, by Teulat, et al [42] and Honsdorf, et al [13] for WC on chromosomes 1H, 6H and 7H and by Diab, et al [43] and Chen, et al [44] for WUE on chromosomes 3H, 5H, 6H and 7H.…”
Section: Introductionmentioning
confidence: 99%